The Rise of 3D-Printing and its Implications with Intellectual Property Rights - Al-Busaidi, Azzan (2017)
This dissertation is about the rise of 3D printing or additive manufacturing in many industries today. The research seeks to go through several industries that have been effected by the technology as well as the emergence of new sectors. Intellectual Property Rights are linked to the success of many industries and many fear 3D printing might diminish that. In order to understand if we are heading that way, an online survey was conducted to gather consumer behaviours. The research seeks to investigate if 3D printing will head in a similar direction as the Music industry.